2016
DOI: 10.1016/j.cmi.2016.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogeny of Shiga toxin–producing Escherichia coli isolates obtained from two Dutch regions using whole genome sequencing

Abstract: Shiga toxin-producing Escherichia coli (STEC) is one of the major causes of human gastrointestinal disease and has been implicated in sporadic cases and outbreaks of diarrhoea, haemorrhagic colitis and haemolytic uremic syndrome worldwide. In this study, we determined the molecular characteristics and phylogenetic relationship of STEC isolates, and their genetic diversity was compared to that of other E. coli populations. Whole genome sequencing was performed on 132 clinical STEC isolates obtained from the fae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
61
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 38 publications
7
61
1
3
Order By: Relevance
“…MLST has been proposed as an adequate tool for producing genetic profiles for a vast number of isolates, especially under non-epidemic circumstances (Ferdous et al, 2016). In this study, a substantial genetic diversity was observed in 301 non-O157 STEC isolates collected from various sources.…”
Section: Discussionmentioning
confidence: 99%
“…MLST has been proposed as an adequate tool for producing genetic profiles for a vast number of isolates, especially under non-epidemic circumstances (Ferdous et al, 2016). In this study, a substantial genetic diversity was observed in 301 non-O157 STEC isolates collected from various sources.…”
Section: Discussionmentioning
confidence: 99%
“…wgMLST was shown to have higher discriminatory power and typeability than in silico MLST. After the introduction of WGS as a typing tool with high potential, gene-by-gene comparison of WGS data has been applied successfully for several species in outbreak settings (22)(23)(24)(25)(26)(27). To our knowledge, this large multicenter study is the first to apply wgMLST for typing of Enterobacteriaceae in nonoutbreak settings and to include a comprehensive evaluation of its performance in a large collection of isolates without a clear epidemiological link.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome multilocus sequence typing (wgMLST) is a WGS-based typing method that extends MLST to the genome level (20). Today, such gene-bygene comparison of WGS data has been applied successfully for several species in outbreak settings, but data for Enterobacteriaceae and nonoutbreak settings are still limited (22)(23)(24)(25)(26)(27). The aim of this study was to develop representative wgMLST schemes for the Citation Kluytmans-van den Bergh MFQ, Rossen JWA, Bruijning-Verhagen PCJ, Bonten MJM, Friedrich AW, Vandenbroucke-Grauls CMJE, Willems RJL, Kluytmans JAJW, on behalf of the SoM Study Group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…coli has not only high serotype diversity but also high genome plasticity. About 1,200 genes define its conserved core genome, but the pan-genome contains more than 13,000 gene families, and the number is still growing (25)(26)(27). In STEC, this is in part due to several major virulence factors being located on transmissible genetic elements like plasmids, pathogenicity islands, or bacteriophages.…”
mentioning
confidence: 99%